The Effect of Cage Stocking Density on Growth, Slaughtering and Carcass Characteristics of Rock Partridges (A. Graeca) - Esen, Fikret; Ozdemir, Gokce; Ozbey, Orhan (International Journal of Poultry Science, 2005)
This study was made to determine the effect of cage stocking density on growth, feed consumption and, slaughter and carcass characteristics of rock partridges (A. Graeca). In the study, 135 rock partridge chicks at 4 weeks of age were separated into 3 different placing groups (Two sub groups of 25, two subgroups of 20 and three subgroups of 15 partidges). Group I was gathered in an area of 25 partridges/m2, Group II in an area of 20 partridges/m2 and Group III in an area of 15 partridges/m2. As a result, in Groups I, II and III, partridge weights were found to be 453.06, 446.04 and 444.36 g, feed benefit ratios were 5.84, 6.26 and 6.10; life strength values were 92.00%, 95.00% and 91.11%; carcass output were 72.11%, 72.42% and 73.68%, respectively . The differences between the groups were not statistically significant. Cage stocking density was there fore observed not to have an effect on these parameters.